Outdoor education toward personal & social responsibility and physical fitness level - Dery rimasa rimasa; Eka Nugraha; Muhammad Faisal Ansari Nasution (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2022)
The research aims to determine the impact of outdoor education activities on personal & social responsibility and physical fitness. The research method used was a Quasi-Experimental design Non-equivalent Control-Group design. The sample consisted of 40 students, then divided into two groups, the experimental group, and the control group. The instrument used was a questionnaire of Personal & Social Responsibility and a Bleep test. The analysis of the experimental group affects Personal & Social Responsibility and Physical Fitness. The results of analysis and calculation state that the Personal & Social Responsibility and physical fitness level experimental group increased compared to the control group and improving the physical fitness level of the experimental group increased by an average of 1.83 compared with the control group with an average of 0.055. In conclusion, the activity of Outdoor Education has increased the Personal & Social Responsibility and physical fitness of students.